A walk in the woods : rediscovering America on the Appalachian Trail - Bryson, Bill (Broadway Books, 1998)
Bryson share his experiences hiking the Appalachian Trail with a childhood friend. The two encounter eccentric characters, a blizzard, getting lost, and rude yuppies along the way.